Ambient Air Pollution and Early Manifestation of Type 1 Diabetes. Issue 3 (May 2015) - Beyerlein, Andreas; Krasmann, Miriam; Thiering, Elisabeth; Kusian, Dennis; Markevych, Iana; D'Orlando, Orietta; Warncke, Katharina; Jochner, Susanne; Heinrich, Joachim; Ziegler, Anette-Gabriele
Abstract : Supplemental Digital Content is available in the text.